Characteristic of anaerobic digestion from slaughterhouse waste - Norazian, Mohamed Noor; Masitah, Hassan; Mohd Kamal, Ulum; Mohd Mustafa Al Bakri, Abdullah (Universiti Teknologi Malaysia (UTM), 2011)
2nd International Conference and Workshops on Basic and Applied Sciences (2nd ICOWOBAS) & Regional Annual Fundamental Science Seminar (RAFSS) 2009 organized by Universiti Teknologi Malaysia from 2nd - 4th June 2009 at The Zone Regency Hotel, Johor Bharu, Johor, Malaysia.